2004
DOI: 10.1096/fj.04-1930fje
|View full text |Cite
|
Sign up to set email alerts
|

Apelin (65‐77) activates p70 S6 kinase and is mitogenic for umbilical endothelial cells

Abstract: We report here that apelin (65-77) activates p70 S6 kinase (p70S6K), not only in CHO cells that have been stably transfected with the apelin receptor, but also in umbilical endothelial cells (HUVEC), which express it endogenously. Apelin (65-77) induces a time-dependent phosphorylation of p70S6K at residues T421/S424 and T389. This dual phosphorylation is associated with two transduction cascades, involving a PI3K pathway and an ERK pathway, respectively. The PI3K pathway, which can be blocked by wortmannin, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
146
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(161 citation statements)
references
References 54 publications
11
146
1
1
Order By: Relevance
“…This PTX-resistant response occurs in a short window of time between 10 and 20 min after stimulation and disappears in the long-term sustained ERK1/2. This was in contrast with the complete abrogation by PTX treatment of the pE13F-induced ERK phosphorylation (13,52), which is in line with the observed lower efficiency of pE13F as compared with K17F to induce ApelinR internalization and to decrease BP (14). In addition, the PTX-resistant ERK1/2 phosphorylation evoked by K17F was completely blocked by ␤-arrestin-2-K296A, which does not bind ERK1/2 efficiently (51).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This PTX-resistant response occurs in a short window of time between 10 and 20 min after stimulation and disappears in the long-term sustained ERK1/2. This was in contrast with the complete abrogation by PTX treatment of the pE13F-induced ERK phosphorylation (13,52), which is in line with the observed lower efficiency of pE13F as compared with K17F to induce ApelinR internalization and to decrease BP (14). In addition, the PTX-resistant ERK1/2 phosphorylation evoked by K17F was completely blocked by ␤-arrestin-2-K296A, which does not bind ERK1/2 efficiently (51).…”
Section: Discussionmentioning
confidence: 72%
“…They similarly inhibit forskolin-induced cAMP production in eukaryotic cells stably expressing either the human (6,11) or the rat ApelinR (4,10). Both peptides promote phosphorylation of ERKs, Akt, and p70 S6 kinase (13) and are highly potent inducers of ApelinR internalization in a clathrin-dependent manner (14 -16). It is important to underline that K17F induces internalization of rat apelin receptor more efficiently than pE13F by a factor of 30 (14).…”
mentioning
confidence: 99%
“…GPCRs are the estimated targets of nearly half of all currently available clinically used drugs [11] and are key components of the signal transduction machinery [35]. Binding of apelin to APJ activates second messenger signaling cascades after coupling to G proteins, which results in activation of central signaling molecules such as mitogen-activated protein kinases (MAPKs) and the PI3K/AKT pathway that are responsible to instigate multiple biological responses [1,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In CHO cells expressing the murine apelin receptor, we showed that apelin-(65-77) also activates extracellular-regulated kinases (ERK) via a pertussis toxin (PTX)-* The costs of publication of this article were defrayed in part by the payment of page sensitive G protein (23). We recently demonstrated, in the same cells, that apelin-(65-77) also induces the activation of p70S6 kinase via two intracellular cascades, ERK-dependent and phosphatidylinositol 3-kinase/Akt-dependent, respectively, which are linked to the phosphorylation of different subsets of threonine or serine residues (24). Accordingly, the regulation of intracellular effectors has been principally analyzed after stimulation of apelin receptor by the short fragment, apelin-(65-77).…”
mentioning
confidence: 99%